Prevalence and Prognostic Significance of Apparent Treatment Resistant Hypertension in Chronic Kidney Disease: Report From the Chronic Renal Insufficiency Cohort Study. Issue 2 (February 2016) - Thomas, George; Xie, Dawei; Chen, Hsiang-Yu; Anderson, Amanda H.; Appel, Lawrence J.; Bodana, Shirisha; Brecklin, Carolyn S.; Drawz, Paul; Flack, John M.; Miller, Edgar R.; Steigerwalt, Susan P.; Townsend, Raymond R.; et al.
Abstract : The association between apparent treatment resistant hypertension (ATRH) and clinical outcomes is not well studied in chronic kidney disease. We analyzed data on 3367 hypertensive participants in the Chronic Renal Insufficiency Cohort (CRIC) to determine prevalence, associations, and clinical outcomes of ATRH in nondialysis chronic kidney disease patients. ATRH was defined as blood pressure ≥140/90 mm Hg on ≥3 antihypertensives, or use of ≥4 antihypertensives with blood pressure at goal at baseline visit. Prevalence of ATRH was 40.4%. Older age, male sex, black race, diabetes mellitus, and higher body mass index were independently associated with higher odds of having ATRH. Participants with ATRH had a higher risk of clinical events than participants without ATRH—composite of myocardial infarction, stroke, peripheral arterial disease, congestive heart failure (CHF), and all-cause mortality (hazard ratio [95% confidence interval], 1.38 [1.22–1.56]); renal events (1.28 [1.11–1.46]); CHF (1.66 [1.38–2.00]); and all-cause mortality (1.24 [1.06–1.45]). The subset of participants with ATRH and blood pressure at goal on ≥4 medications also had higher risk for composite of myocardial infarction, stroke, peripheral arterial disease, CHF, and all-cause mortality (hazard ratio [95% confidence interval], (1.30 [1.12–1.51]) and CHF (1.59 [1.28–1.99]) than those without ATRH. ATRH was associated with significantly higher risk for CHF and renal events only among those with estimated glomerular filtration rate ≥30 mL/min per 1.73 m 2 . Our findings show that ATRH is common and associated with high risk of adverse outcomes in a cohort of patients with chronic kidney disease. This underscores the need for early identification and management of patients with ATRH and chronic kidney disease. Abstract : Supplemental Digital Content is available in the text.